Dysfunctional Innate Immune Responses and Severe Dengue - Malavige, Gathsaurie Neelika; Jeewandara, Chandima; Ogg, Graham S. (Frontiers in Cellular and Infection Microbiology, 2020)
Although infection with the dengue virus (DENV) causes severe dengue, it causes a mild self-limiting illness in the majority of individuals. There is emerging evidence that an aberrant immune response in the initial stages of infection lead to severe disease. Many inflammatory cytokines, chemokines and lipid mediators are significantly higher in patients with severe dengue compared to those who develop mild infection, during febrile phase of illness. Monocytes, mast cells and many other cells of the immune system, when infected with the DENV, especially in the presence of poorly neutralizing antibodies, leads to production of proinflammatory cytokines and inhibition of interferon signaling pathways. In addition, production of immunosuppressive cytokines such as IL-10 further leads to inhibition of cellular antiviral responses. This dysregulated and aberrant immune response leads to reduced clearance of the virus, and severe dengue by inducing a vascular leak and excessive inflammation due to high levels of inflammatory cytokines. Individuals with comorbid illnesses could be prone to more severe dengue due to low grade endotoxaemia, gut microbial dysbiosis and an altered phenotype of innate immune cells. The immunosuppressive and inflammatory lipid mediators and altered phenotype of monocytes are likely to further act on T cells and B cells leading to an impaired adaptive immune response to the virus. Therefore, in order to identify therapeutic targets for treatment of dengue, it would be important to further characterize these mechanisms in order for early intervention. In this review, we discuss the differences in the innate immune responses in those who progress to develop severe dengue, compared to those with milder disease in order to understand the mechanisms that lead to severe dengue.